508. High Rates of Cure and Long-Term Symptom Resolution With Both Capsule and Lower Gastrointestinal Fecal Microbiota Transplantation for Recurrent Clostridium difficile Infection. (26th November 2018) - Shull, Hannah; Martin, Elise; Grogan, Tristan; Chen, Lucia; Uslan, Daniel Z
Abstract: Background: Fecal microbiota transplantation (FMT) is the treatment of choice for recurrent C. difficile infection (CDI), but limited data exist on long-term real world outcomes of FMT and optimal routes of administration. Methods: We performed a survey of patients who received FMT for CDI at UCLA Health. The online survey was adapted from the NIH PROMIS gastroenterology (GI) symptom scale to assess various GI symptoms in the week prior to FMT and the week prior to taking the survey (long-term follow-up). Additional questions addressed route of FMT, timing of improvement, and recurrence of symptoms or CDI. Chart review provided demographic information and time to follow-up. Changes (pre/post) were assessed using the Wilcoxon signed-rank test. Results: Ninety-six FMTs were performed from December 2014 through September 2017. Forty-five of 88 alive patients completed the survey (response rate 51.1%). Ages ranged from 18 to 90 years old (average 61.2 years, SD 18.0). Time from FMT to survey completion ranged from 14 to 1, 044 days (average 526 days, SD 253.9). Route of initial FMT included 14 capsule and 31 lower GI tract FMTs (28 colonoscopies, threeother). Five patients had a second FMT after initial failure (second FMTs: one capsule and four colonoscopy). In total, we included 50 FMTs (15 capsule [30%] and 35 lower [70%]). Overall success rate was 76% (38/50), with 10 failed FMTs (20%) and 2 of unclear outcome. There was a higher success rate of lower FMTs at 85.7% (30/35) compared with capsule at 66.7% (10/15), but this difference was not statistically significant ( P = 0.312). Comparing GI symptoms pre- and post-FMT, there was a statistically significant decrease in days with diarrhea ( P < 0.001), frequency and severity of abdominal pain (both P < 0.001), bloated feeling ( P < 0.001), and improvement in appetite ( P < 0.001) at long-term follow-up. Comparing capsule vs. lower FMTs, post-FMT symptoms appeared similar. Conclusion: FMT led to a high rate of long-term cure, with significant improvement in multiple GI symptoms months to years after transplant. The route of FMT did not impact symptom relief, but there was a higher rate of failure with capsule FMT compared with lower FMTs. More studies are needed to understand the impact of routes of FMTs on long-term outcomes of patients with CDI. Disclosures: E. Martin, Pfizer: Investigator, Salary.